Solution of stochastic delay differential equation on asset value changes for capital market price - Uchechukwu*, C.F.; Amadi†, I.U.; Azor‡, P.A. (International Journal of Mathematical Analysis and Modelling, 2023)
An asset values in trading business creates opportunity where returns or profits would be used at every periods. As a result, a stochastic model of asset value function is considered only in periodic events. Close form analytical solutions were obtained which gave precise measures and conditions of generating asset values through additive effects series. The effects of time delay for all periods were critically examined. Normality tests were conducted to show the impact analysis of initial stock prices and asset values that followed some probability distributions. To this end, the Tables, graphs and other stock quantities were discussed for the purpose of investment plans as it affects asset value functions.